An Islam of her own : reconsidering religion and secularism in women's Islamic movements - Hafez, Sherine (New York University Press, 2011)
"As the world grapples with issues of religious fanaticism, extremist politics, and rampant violence that seek justification in either "religious" or "secular" discourses, women who claim Islam as a vehicle for individual and social change are often either regarded as pious subjects who subscribe to an ideology that denies them many modern freedoms, or as feminist subjects who seek empowerment only through rejecting religion and adopting secularist discourses. Such assumptions emerge from a common trend in the literature to categorize the 'secular' and the 'religious' as polarizing categories, which in turn mitigates the identities, experiences and actions of women in Islamic societies. Yet in actuality Muslim women whose activism is grounded in Islam draw equally on principles associated with secularism."--